Folk Songs and Social Realities: The Nsude Igbo Women Example - Nnamdi-Eruchalu, Geraldine Ifesinachi (Advances in Social Sciences Research Journal, 2022)
This study is aimed at documenting and analyzing the folk songs of Nsude women of South East Nigeria with the aim of understanding and reconstructing the traditional culture of the people which is shrinking in the face of westernization. The researcher observed that Christian songs and popular music have taken over the roles women previously performed by folk songs. The study argues that the decline in the use of folk songs by the womenfolk could be depriving the younger generations of the people certain values, beliefs, norms, and social practice which hitherto controlled behaviour and held the traditional society together, and as such stripping them of their culture and identity. Previous works on Igbo folk songs focused on documentation only, and some on the pedagogical roles of folk music. The present study addresses the folk songs sang by Nsude women so as to highlight the peculiarities of the people’s existence and philosophies.The songs were recorded from the researcher’s interaction with five elderly women from the town, as well as from her introspection. The analysis revealed that the songs in addition to being sources of enjoyment, entertainment and relaxation for all inculcates in the people the values to uphold and the vices to abhor for the harmonious existence of the community.